2001
DOI: 10.1364/oe.9.000687
|View full text |Cite
|
Sign up to set email alerts
|

Designing the properties of dispersion-flattened photonic crystal fibers

Abstract: We present a systematic study of group-velocity-dispersion properties in photonic crystal fibers (PCF's). This analysis includes a thorough description of the dependence of the fiber geometrical dispersion on the structural parameters of a PCF. The interplay between material dispersion and geometrical dispersion allows us to established a well-defined procedure to design specific predetermined dispersion profiles. We focus on flattened, or even ultraflattened, dispersion behaviors both in the telecommunication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(139 citation statements)
references
References 8 publications
7
132
0
Order By: Relevance
“…However, since the pump wavelength is closer to the ZDW of the material, dispersion flattened fibers should be possible, and we might expect significantly more broadening using optimised dispersion design algorithms previously developed for silica-based MOF fabrication 46 to develop suitable fiber structures for compound glasses. Since the material damage thresholds of the glasses are not yet well understood, reducing the threshold peak intensity required for continuum generation could be an important practical consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the pump wavelength is closer to the ZDW of the material, dispersion flattened fibers should be possible, and we might expect significantly more broadening using optimised dispersion design algorithms previously developed for silica-based MOF fabrication 46 to develop suitable fiber structures for compound glasses. Since the material damage thresholds of the glasses are not yet well understood, reducing the threshold peak intensity required for continuum generation could be an important practical consideration.…”
Section: Discussionmentioning
confidence: 99%
“…5(a) In order to analyze the dispersion properties of PQFs based in the Thue-Morse sequence, we have simulated a number of different direct and inverse designs by changing the equivalent quasiperiod, Λ, the hole radius of the aperiodic lattice, a, and the hole radius of the defects, b. In this way, by analyzing the dispersion curves of these different PQFs, we have found that it is possible to control their dispersion characteristics following a procedure similar to that described in [28]. The group velocity dispersion, D, including the material dispersion, can be evaluated as…”
Section: Guiding and Dispersion Propertiesmentioning
confidence: 99%
“…Hydrostatic pressure sensors based on birefringent fibers are not compact since they usually need non-fiber components to detect the pressure-induced phase or use the fiber Sagnac interferometer with a relatively long sensing fiber. PCFs [28][29][30][31][32] are the great success in the history of optical fibers, which have achieved excellent properties in birefringence [33][34][35][36][37][38][39][40], dispersion [41][42][43][44][45][46][47][48][49][50][51], single polarization single mode [52][53][54], nonlinearity [55], and effective mode area [56][57][58], and also excellent performances in the applications of fiber lasers [59][60][61] and nonlinear optics [62][63][64][65] over the past several years. PCFs have also further improved optical fiber sensors and have been used for strain sensing [66], gas sensing [67], biochemical sensing [68], refractive index sensing [69] and temperature sensing [70].…”
Section: Introductionmentioning
confidence: 99%